Media Power and the Rule of Law in the Rise of New Despotism: Lesson Learned from Indonesia, China, Russia, and Iran - Siti Raudhah Salma (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: this study aims to seek an answer to these research questions: 1) "How do media power and the rule of law influence the rise of new despotism in Indonesia, China, Russia, and Iran?" and 2) "How does the new despotism affect the practice of good governance accountability principle in those countries?". This research attempts to identify the rise of new despotism in the world. It contributes to examining the implications of government policies regarding this phenomenonMethod: Multiple case study approaches from these countries are used to conduct qualitative research. Result: The results respond to the call for new thinking about the concept of "New Despotism" in order to contribute to further studies regarding new despotism in developing countries. In addition, the findings of this research are expected to assist policymakers in developing and evaluating policies that address this circumstance. Conclusion: This research can help to rebuild the accountability principle of a good governance system. Accountability in the context of public administration is being investigated since it is at the heart of government administration practice. It has long been a source of worry, particularly in policy-making.